Matchplay characteristics and performance indicators of male junior and entry professional tennis players - Filipcic, A.; Leskosek, B.; Crespo, M.; Filipcic, T. (International Journal of Sports Science & Coaching, 2021)
Performance analysis during match play is vital for the long-term development of tennis players. The primary goal of this study was to establish the differences between junior and entry professional tennis player's selected performance indicators in five-game situations. Data were collected using the Sagit/Tennis tracking system during six junior and four professional tennis matches. Eight boys performed 3,112 strokes, while eight male professional players hit 1,631 strokes. The results showed slight differences in the distance covered by the two observed groups in the specific game situations. Professional players performed faster shots in all game situations, except when playing at the net. They played at a significantly faster tempo than the juniors. This difference was also affected by the higher shots speed and shorter distance between the two players during the rallies. When playing from the baseline, the entry professional players performed shots at a smaller angle than the juniors; and when serving, receiving and playing at the net, they hit shots at a greater angle than the juniors. Our findings may assist coaches and players in improving the effectiveness of their tactical and technical training to enhance their competitive performance.